Relation between iodine nutrition and thyroid diseases in Qinghai, China - Fan, Xiaoxia; Zhao, Lingling; Wang, Shuqiong; Song, Kang; Wang, Beibei; Xie, Yanling; Jiang, Yanping; Lin, Lijun; Teng, Weiping; Cai, Chunmei; Yao, Yongli (Frontiers in Endocrinology, 2023)
INTRODUCTION 1. Research method 1.1 Sampling method 1.1.1 Thyroid ultrasound examination 1.1.2 Thyroid function 1.1.3 Urine iodine level detection 1.2 Definition of disease 1.3 Diagnostic criteria 1.4 Statistical analysis 2 Research results 2.1 General situation of survey objects 2.2 Urine iodine test results and iodized salt coverage rate in adults 2.3 Comparison of iodine nutrition status among adults and different genders and regions 2.4 Detection of thyroid diseases in adults 2.5 Thyroid diseases and iodine nutritional status Discussion rural areas, and that of hypothyroidism, subclinical hypothyroidism, and goiter was lower than that in rural populations. The detection rate of clinical hypothyroidism was statistically significant in different iodine nutritional states (P< 0.05).